PERLINDUNGAN HUKUM TERHADAP PENGGUNA PINJAMAN ONLINE (PINJOL) ILEGAL - Rayyan Sugangga; Erwin Hari Sentoso (Universitas Pakuan, 2020)
ABSTRACT In the last few years to date, OJK which is part of the Investment Alert Task Force is still found and is using illegal online loan services. Pinjol illegal online besides can not be controlled, many of which cause problems for its users, some problems lead to the related borrowers who are not strongly collected by debt collectors. This article uses the normative legal research method while still paying attention to empirical / sociological / non-doctrinal / social-legal legal research. The results of the study found that loans through illegal online loans do not require user payments, then also research results in other countries can be used to overcome the difficulties of these illegal loans.Keywords: Illegal Online Loans, User Protection, User Awareness ABSTRAK Dalam beberapa tahun terakhir hingga saat ini, OJK yang tergabung dalam Satgas Waspada Investasi masih menemukan dan memblokir layanan pinjaman online ilegal. Pinjol online ilegal ini selain tidak dapat dikontrol, banyak menimbulkan masalah bagi penggunanya, beberapa kasus berujung ke peminjam yang mengakhiri hidupnya karena tidak kuat ditagih oleh debt collector. Artikel ini menggunakan metode penelitian hukum normatif dengan tetap memperhatikan penelitian hukum empiris/sosiologis/non doctrinal/socio-legal. Hasil penelitian menemukan bahwa peminjaman melalui pinjol online ilegal tidak menghilangkan kewajiban pembayaran hutang pengguna, lalu juga terdapat hasil perbandingan di negara lain yang dapat diadopsi untuk mengatasi permasalahan pinjol ilegal ini.Kata Kunci : Pinjaman Online Ilegal, Perlindungan Pengguna, Kesadaran Pengguna